2017
DOI: 10.15330/pcss.18.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and Self-Supporting Burning of Gas-Air Mixtures with Hydrogen Admixtures on Platinum Wire

Abstract: The proposed work describes analytical identification of hydrogen admixture concentration and catalyst temperatures limit values beyond which catalytic flameless steady combustion of gas-air mixtures at ambient temperature at platinum wires is observed. Effect of gas-air slip velocity upon considered values is shown. Initial platinum wire preheating temperatures required for catalytic ignition are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…In [7] it was experimentally shown that if the combustible gas impurity concentration is higher than some critical value, then after switching off the electric current the catalytic combustion of hydrogen or ammonia in a cold gas mixture on a thin platinum wire becomes Electric Resistence Hysteresis of Platinum Filament in Cold Air/Hydrogen Mixtures 421 self-supporting. In [12], the limit values of hydrogen impurity concentration and catalyst temperature are analytically found, above which the catalytic flameless self-supporting stable combustion of gas-air mixtures of room temperature on platinum wire is observed.…”
Section: Introductionmentioning
confidence: 98%
“…In [7] it was experimentally shown that if the combustible gas impurity concentration is higher than some critical value, then after switching off the electric current the catalytic combustion of hydrogen or ammonia in a cold gas mixture on a thin platinum wire becomes Electric Resistence Hysteresis of Platinum Filament in Cold Air/Hydrogen Mixtures 421 self-supporting. In [12], the limit values of hydrogen impurity concentration and catalyst temperature are analytically found, above which the catalytic flameless self-supporting stable combustion of gas-air mixtures of room temperature on platinum wire is observed.…”
Section: Introductionmentioning
confidence: 98%
“…5 • 1 0 6 1 / c , При деякому значенні концентрації Y f.sb (sb -self-supporting burning) горючого газу критичне значення сили струму погасання зменшується до нуля. Тоді при концентраціях горючого газу Y f. >Y f.sb при вимкненні сили струму каталітичне горіння продовжується (самопідтримується) [15].…”
unclassified